Brazilian guidelines on chronic venous disease of the Brazilian Society of Angiology and Vascular Surgery - Rodrigo Kikuchi; Claudio Nhuch; Daniel Autran Burlier Drummond; Fabricio Rodrigues Santiago; Felipe Coelho Neto; Fernanda de Oliveira Mauro; Fernando Trés Silveira; Guilherme Peralta Peçanha; Ivanesio Merlo; Jose Marcelo Corassa; Leonardo Stambowsky; Marcondes Figueiredo; et al. (Jornal Vascular Brasileiro, 2023)
Abstract The Brazilian Society of Angiology and Vascular Surgery has set up a committee to provide new evidence-based recommendations for patient care associated with chronic venous insufficiency. Topics were divided in five groups: 1. Classification, 2. Diagnosis, 3. Conservative or non-invasive treatment, 4. Invasive treatment and 5. Treatment of small vessels. This last series is closely related to the activities of Brazilian angiologists and vascular surgeons, who are heavily involved in the treatment of small superficial veins. These guidelines are intended to assist in clinical decision-making for attending physicians and health managers. The decision to follow a guideline recommendation should be made by the responsible physician on a case-by-case basis taking into account the patient's specific condition, as well as local resources, regulations, laws, and clinical practice recommendations.